Pengembangan Bahan Ajar LKS Elektronik Menggunakan Model Pembelajaran Search Solve Create Share Berbantuan FlipHTML5 Pada Materi Mikroprosesor Kelas XI TAV di SMKN 5 Jakarta - JVOTE, Admin; Nurmalasari, Siti; Sukardjo, Mochammad; Bintoro, Jusuf (JURNAL PENDIDIKAN VOKASIONAL TEKNIK ELEKTRONIKA (JVoTE), 2022)
Learning activities that are in appropriate with the curriculum require several component, one of them is teaching materials. Teacher have an importan role to selection of teaching materials that will be used to achieve learning purpose. In this research an electronic student worksheet was developed using Search Solve Create Share (SSCS) model learning assist by FlipHTML5 in microprocessor lesson for class XI Audio Video Engineering at SMKN 5 Jakarta. This research uses Reseach and Development method with the 4D model consisting of for steps, namely Define, Design, Development, and Disseminate, nonetheless this research is limited to development stage. The result of this research is (1) Electronic student worksheet uses SSCS model learning developed based on the R&D method with the 4D model; (2) The student worksheet feasibility test by material experts, linguists expert, instructional design expert, media experts with the results of the assesment was classified as highly feasibility; (3) Testing the student worksheet to student through one-to- one trials and small groups trials with the result of the assesment was classified as highly feasibility.